2021
DOI: 10.6007/ijarbss/v11-i8/10418
|View full text |Cite
|
Sign up to set email alerts
|

Parents Involvement in Implementation of Career Transition for Students with Learning Disabilities from a Teacher’s Perspective in Malaysia

Abstract: Parents' involvement is one factor that contributes to implementing career transition for students with learning disabilities (SLD) in the Special Education Integration Program (SEIP). The involvement in educating children at school could also nurture their psychological growth, sharing learning experiences, supporting and respecting the teachers' effort. This research explored parents' involvement and the obstacles they face in implementing career transition for students with learning disabilities (SLD) in Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…This finding is in line with Nor and Yasin (2018) study whereby only 40% parents attended IEP planning. Although study of Abdullah and Ibrahim (2021) proved that family engagement in rural areas is higher comparing to urban areas, however, this study finds the otherwise. Based on Zainal & Hashim (2019) analyse, it was found that parents are too busy with their work, thus they have no time to take part in school activities.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…This finding is in line with Nor and Yasin (2018) study whereby only 40% parents attended IEP planning. Although study of Abdullah and Ibrahim (2021) proved that family engagement in rural areas is higher comparing to urban areas, however, this study finds the otherwise. Based on Zainal & Hashim (2019) analyse, it was found that parents are too busy with their work, thus they have no time to take part in school activities.…”
Section: Discussioncontrasting
confidence: 72%
“…In the process of preparing IEP for CTP, it is found that SSEN cannot understand themselves (Abdullah & Ibrahim, 2021) and lack confidence in their knowledge of the world of work (Mehta-Diston, 2018). In the study of Nor & Yassin (2018), it is found that 96.6% parents agree that parents should be open to express their opinions for the benefit of their children.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The active participation of parents in their children's education has been recognized as an essential component for the success of special education programs [1][2][3][4]. However, there are challenges and complexities in fostering effective parental involvement [1].…”
Section: Introductionmentioning
confidence: 99%
“…The active participation of parents in their children's education has been recognized as an essential component for the success of special education programs [1][2][3][4]. However, there are challenges and complexities in fostering effective parental involvement [1]. Their active participation and collaboration with educational institutions are key aspects of guaranteeing an optimal education adapted to the specific needs of each child [5].…”
Section: Introductionmentioning
confidence: 99%